Kajian Kebutuhan Terminal Tipe A di Tanjung Selor Provinsi Kalimantan Utara - Arbie Sianipar (Sekretariat Badan Kebijakan Transportasi, Formerly by Puslitbang Transportasi Laut, Sungai, Danau, dan Penyeberangan, 2021)
ABSTRACTNeeds Assessment of Type A Terminal in Tanjung Selor North Kalimantan Province: In PM No. 132 of 2015 concerning the Operation of Road Transport Passenger Terminals Article 8, passenger terminals according to their service roles are grouped into types consisting of Types A, B, and C. Where Type A serves ALBN/AKAP/ADKP/Angkot/Angdes. The city of Tanjung Selor as the capital of North Kalimantan Province which has an important and strategic position and role in regional and national development does not yet have a Type A Terminal. The research purpose is to formulate recommendations for the level of need for type A terminals in North Kalimantan Province. The research method used in this research is descriptive quantitative by conducting a survey of the origin of the purpose of the trip. Based on analysis & discussion The number of Tanjung Selor-Tanjung Redep-Samarinda-Balikpapan trips is 169 trips and vice versa 148 trips, so in this case it requires a fleet with the Tanjung Selor-Tanjung Redep-Samarinda-Balikpapan route as many as 15 units (8 from Tanjung Selor & Balikpakan 7 units). The need for a Type A Terminal in North Kalimantan, especially in Bulungan Regency, is very urgent, currently the Tanjung Selor - Tanjung Redep Damri bus is served from the market location because North Kalimantan does not yet have a Terminal and the Type A Terminal Class for Tanjung Selor City based on the results of the analysis is class 3. There needs to be compatibility between the AKDP & Angkot/Angdes Routes as the connectivity of the Type A Terminal. Need a stimulus from the Government & Local Government so that more investors invest in the AKAP sector so that the level of connectivity in North Kalimantan increases. Directorate General of Land Transportation to immediately make FS & its derivatives so that the implementation of the Type A Terminal construction can be realized immediately.Keywords: Bus Station Type A; AKAP Transportation; Accessibility.ABSTRAKDalam PM No 132 Tahun 2015 tentang Penyelenggaraan Terminal Penumpang Angkutan Jalan Pasal 8, terminal penumpang menurut peran pelayanannya dikelompokkan dalam tipe yang terdiri atas Tipe A, B, dan C. Dimana Tipe A melayani ALBN/AKAP/ADKP/Angkot/Angdes. Kota Tanjung Selor sebagai ibukota Provinsi Kalimantan Utara yang memiliki posisi dan peranan yang penting dan strategis dalam pembangunan daerah maupun nasional belum memiliki Terminal Tipe A. Tujuan penelitian ini adalah tersusunnya rekomendasi tingkat kebutuhan terminal tipe A di Provinsi Kalimantan Utara. Metode penelitian yang digunakan dalam penelitian ini adalah deskriptif kuantitatif dengan melakukan survei asal tujuan perjalanan. Berdasarkan analisis & pembahasan jumlah perjalanan Tanjung Selor-Tanjung Redep-Samarinda-Balikpapan sebanyak 169 perjalanan begitu juga sebaliknya 148 perjalanan, maka dalam hal ini membutuhkan armada dengan trayek Tanjung Selor-Tanjung Redep-Samarinda-Balikpapan sebanyak 15 unit (8 dari Tanjung Selor & Balikpakan 7 unit). Kebutuhan Terminal Tipe A di Kalimantan Utara khususnya di Kabupaten Bulungan sudah sangat mendesak. Saat ini bus Damri Tanjung Selor – Tanjung Redep dilayani dari lokasi pasar karena di Kalimantan Utara belum memiliki terminal dan kelas terminal Tipe A untuk Kota Tanjung Selor berdasarkan hasil analisis adalah Kelas 3. Perlu kesesuaian trayek AKDP & Angkot/Angdes sebagai konektivitas Terminal Tipe A tersebut. Perlu stimulus dari Pemerintah Pusat & Pemerintah Setempat agar banyak investor yang berinvestasi di bidang AKAP sehingga tingkat konektivitas Kalimantan Utara meningkat; Ditjen Perhubungan Darat agar segera membuat FS & turunannya agar pelaksanaan pembangunan Terminal Tipe A segera direalisasikan.Kata kunci:Terminal Bus Tipe A; Angkutan AKAP; Aksesibilitas.